The historical maps in the student´s book of São Paulo State. (Revista Contexto & Educação, 2023)
Not only interdisciplinary, Cartography has also become of daily importance at school. However, there is a certain knowledge which should be taught in order to comprehend the map as a language. This is the case of historical maps. They allow students to notice and to analyze the geographical and historical changes, which in turn reflect at the representation of the space, and also to understand geographical concepts.  Today when we refer to the discipline Geography, the didactic material displays many colored printed images which show an advance in the insertion of cartography as a teaching methodology. On the contrary of which was expected however, older maps are not displayed so often and when they appear, they are not used in a functional way. Inside this context there is the didactic material distributed by the Secretaria do de Educação Estado de São Paulo (the Education´s Secretary of the State of São Paulo) to all public schools of the state. This work analyzed historical maps presented in the Geography didactic material mentioned above and the adopted methodologies used to their utilization in the classroom. Interviews with state teachers were conducted. Among the results it was verified an underuse of those maps because of their scarcity in the analyzed material and because of the professional training of the teachers, which result in many obstacles to the utilization of the historical cartography as a knowledge source.